Natural capitalism : creating the next industrial revolution. - Hawken, Paul, 1946-; Lovins, Amory B., 1947-; Lovins, L. Hunter, 1950- (New York : Little and Brown, 1999)
1 The Next Industrial Revolution 2 Reinventing the Wheels: Hypercars and Neighborhoods 3 Waste Not 4 Making the World 5 Building Blocks 6 Tunneling Through the Cost Barrier 7 Muda, Service, and Flow 8 Capital Gains 9 Nature's Filaments 10 Food for Life 11 Aqueous Solutions 12 Climate: Making Sense and Making Money 13 Making Markets Work 14 Human Capitalism 15 Once Upon a Planet Notes References Index